Winter and summer sedimentary dynamic process observations in the sea area off Qinhuangdao in the Bohai Sea, China - Zhang, Deqiang; Pang, Chongguang; Liu, Zhiliang; Jiang, Jingbo (Frontiers in Earth Science, 2023)
Using seabed base observation platform measurements obtained in February 2017 and August 2019, this study examines the winter and summer hydrography and suspended sediment concentration (SSC) in the sea area off Qinhuangdao in the Bohai Sea. In summer, the relatively weak residual currents flowed northeastward and showed little correlation with the wind field, especially in the middle layer of the water column. In winter, the residual currents were strengthened, flowing to the northeast during strong wind periods, and predominantly to the southwest during intermittent periods. Moreover, driven by the pressure gradient force associated with the wind-induced sea surface height variations, the winter current was closely related to the wind speed, with correlation coefficients ranging from 0.4 to 0.6 and a time lag of 10 hours. The summer SSC was lower and mainly controlled by the tidal current, whereas in winter, owing to the enhanced Reynolds stress and turbulent kinetic energy, strong wind bursts triggered significant sediment resuspension and led to a higher SSC. For the suspended sediment flux (SSF), the advection terms contributed more than 80% in the winter and summer, while the vertical circulation terms contributed 13% in winter, and approximately half that much in summer. Generally, the suspended sediment is transported back and forth, with a little net northward and northeastward motions in winter and summer, respectively. This may explain the low SSC sustaining in coastal Qinhuangdao all year round.